Potential of Ration Based on Local Raw Materials as A Substitute of Commercial Ration for Crude Protein, Crude Fat, and Crude Fiber - Fadhli Fajri; Fajri Maulana; Anggun Angkasa Bela Persada; Dwi Sandri; Bunga Putri Febrina; Wenni Meika Lestari; Amelia Lulu Rosalin Hutabarat; Mufrida Zein (AGRITROPICA : Journal of Agricultural Sciences, 2022)
This study aims to determine the potential of rations based on local raw materials as a substitute for commercial rations for crude protein, crude fat, and fiber content. This study uses local feed ingredients in Tanah Laut Regency, South Kalimantan Province: local corn, rice bran, palm kernel cake, fish meal, maggot, stone flour, topmix, and commercial rations with the brand AL 100-II Comfeed produced by PT. Japfa Comfeed Indonesia Tbk. This research method is an experimental method using a completely randomized design (CRD), with five ration treatments and four replications. The treatment rations were A (100% Commercial / Control Ration), B (75% Commercial Ration + 25% Local Ration), C (50% Commercial Ration + 50% Local Ration), D (25 % Commercial Ration + 75% Local Ration) and E (100% Local Basal Ration). The parameters measured were crude protein (%), crude fat (%), and crude fiber (%). The results showed that the nutritional quality of local and factory rations at specific compositions had no significant effect (P>0.05) on crude protein, crude fat, and fiber content. This study concluded that the composition of the mixture of local and commercial rations did not affect the nutritional content, especially crude protein, crude fat, and crude fiber. Crude protein content ranges from 16.87% to 17.96%, crude fat from 5.17% to 6.29%, and crude fiber from 5.17% to 6.29%.